2015
DOI: 10.1002/chir.22563
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Separation of Uncharged Pomalidomide Enantiomers Using Carboxymethyl‐β‐Cyclodextrin: A Validated Capillary Electrophoretic Method

Abstract: The racemic mixture of pomalidomide (POM), a second-generation immunomodulatory uncharged drug, was separated into enantiomers by capillary zone electrophoresis for the first time. Seven different chargeable cyclodextrin (CD) derivatives were screened as complexing agents and chiral selectors, investigating the stability of the POM-CD inclusion complexes and their enantiodiscriminating capacities. Based on preliminary experiments, carboxymethyl-β-CD (CM-β-CD) was found to be the most effective chiral selector.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…Based on the observed retention times on the investigated CSPs (Supporting Information Table S1) the following stability order can be assumed between POM and CDs: ␤-CD > CM-␤-CD> HP-␤-CD>SB-␤-CD. This is in agreement with our previous results regarding the separation of POM enantiomers using charged CDs in CE, where higher complex stabilities were observed, with CM-␤-CD, when compared to SB-␤-CD [12].…”
Section: Chiral Stationary Phase Screeningsupporting
confidence: 93%
“…Based on the observed retention times on the investigated CSPs (Supporting Information Table S1) the following stability order can be assumed between POM and CDs: ␤-CD > CM-␤-CD> HP-␤-CD>SB-␤-CD. This is in agreement with our previous results regarding the separation of POM enantiomers using charged CDs in CE, where higher complex stabilities were observed, with CM-␤-CD, when compared to SB-␤-CD [12].…”
Section: Chiral Stationary Phase Screeningsupporting
confidence: 93%
“…To achieve electrophoretic chiral separation of the uncharged LEN enantiomers, various increasing concentrations (0.2–30 mM) of eight negatively charged, multicomponent CD derivatives were applied, differing in cavity size, type, and number of substituents. Preliminary chiral selector screening was performed with 25 mM Tris‐acetate BGE at pH 5, which also yielded excellent results in our previous studies . The summarized results, presented in Table , reveal that only two CDs displayed chiral interactions with the analyte.…”
Section: Resultsmentioning
confidence: 66%
“…This study, along with some other previously reported studies , suggested that this approach is more reproducible and more favorable, considering the inter‐instrumental transfer capability. CM‐β‐CD also proved to be the most effective CS for several analytes, such as pomalidomide , zopiclone and its active metabolites , propranolol , and 4‐hydroxypropranolol .…”
Section: Chiral Selectorsmentioning
confidence: 99%